Теоретичні основи аналізу зобов’язань суб’єктів господарювання - Стаднюк, Тетяна Володимирівна; Stadnyuk, T. V.; Татушко, Т. А; Tatushko, Т. А (ТОВ "ДКС Центр", 2014)
У статті розглянуто сутність та важливість аналітичної оцінки зобов’язань підприємств. Акцентовано увагу на змінах, регламентованих НП(С)БО 1, які відбулися в структурі балансу та усунули труд¬нощі користувачам фінансової звітності під час оцін¬ки фінансового стану підприємств. Висвітлено підходи вчених щодо аналізу зобов’язань та окреслено послідовність здійснення аналізу даного об’єкта дослідження. The article summarizes with the essence and importance of analytical value of enterprises' obligations. The attention is focused on the changes which are regulated by National Provisions (Standard) Accounting 1, which occurred in the structure of the balance and eliminated the difficulties for users of financial reporting during the assessment of the enterprise's financial condition. Scientific approaches related to the analysis of obligations separated sequence of analysis of the object of study is described.
Theoretical basis of the analysis obligations of business entities
Keywords: зобов’язання; obligations; позиковий капітал; loan capital; аналіз; analysis; фінансова стійкість; financial stability